2013
DOI: 10.1021/am400658h
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene/MWCNT/Graphite Nanoplate Nanocomposites: Efficient Electromagnetic Interference Shielding Material through Graphite Nanoplate–MWCNT–Graphite Nanoplate Networking

Abstract: Today, we stand at the edge of exploring carbon nanotube (CNT) and graphene based polymer nanocomposites as next generation multifunctional materials. However, irrespective of the methods of composite preparation, development of electrical conductivity with high electromagnetic interference (EMI) value at very low loading of CNT and (or) graphene is limited due to poor dispersion of these nanofillers in polymer matrix. Here, we demonstrate a novel technique that involves in-situ polymerization of styrene/multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
174
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 307 publications
(176 citation statements)
references
References 51 publications
2
174
0
Order By: Relevance
“…Shielding materials attenuate the incident EM waves by means of reflection R, multiple reflections M, and absorption (A) [6]: SET = SEA + SER + SEM (4) Figure 6 demonstrates the EMI SE of binary and ternary composites contained 3, 5 and 8 wt% of conductive fillers over the frequency range 8-12 GHz (X-band frequency range). It is obvious that composites based on 8 wt% filler show higher SE, which is attributed to higher concentration and more conductive paths within the polymer matrix that could interact with incident EM waves.…”
Section: Emi Shielding Effectiveness (Se)mentioning
confidence: 99%
See 1 more Smart Citation
“…Shielding materials attenuate the incident EM waves by means of reflection R, multiple reflections M, and absorption (A) [6]: SET = SEA + SER + SEM (4) Figure 6 demonstrates the EMI SE of binary and ternary composites contained 3, 5 and 8 wt% of conductive fillers over the frequency range 8-12 GHz (X-band frequency range). It is obvious that composites based on 8 wt% filler show higher SE, which is attributed to higher concentration and more conductive paths within the polymer matrix that could interact with incident EM waves.…”
Section: Emi Shielding Effectiveness (Se)mentioning
confidence: 99%
“…At a critical volume fraction of conductive filler, electrical conductivity of polymer shows a the transition from insulating to known as percolation threshold concentration (φc) [2]. Recently, composites based on hybridized filler systems comprising fillers with different dimensions and aspect ratio have great attention to the preparation of the electrically conductive polymer composites with low percolation threshold and the potential for manufacturing of electromagnetic interference(EMI) shielding materials [6]. In present work, nanocomposites based on a hybrid system comprising, conductive Carbon black (CB) and Graphite nanoplates (GNP), and silicon rubber matrix were prepared.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Khatua et al 41 reported that the p-p interaction between the nanofiller and polymer facilitates electron transport in the nanocomposites. In our case, the p-p interaction among the CNH, GNP, and phenyl rings of PS can be operative to improve the EMI SE value of the.…”
Section: Article Wileyonlinelibrarycom/appmentioning
confidence: 99%
“…However, there has not been much research about wood-based electromagnetic shielding composites made with the EG. Moreover, microholes in EG result in a situation where incident EM waves are repeatedly reflected at different directions on its surface or in the holes, which make it conducive to attenuation for electromagnetic waves (Maiti et al 2013). Furthermore, its vermicular shape (appears to be a fiber shape) can contribute to mixing with other components uniformly (Kratochvíla et al 2013).…”
Section: Introductionmentioning
confidence: 99%